Measurement of contact parameters on under-platform dampers coupled with blade dynamics. (August 2019) - Umer, Muhammad; Botto, Daniele
Highlights: First time an attempt has been made to associate the macro behavior of the under-platform dampers with the micro behavior of its contact. A new numerical method has been put forward to compute the equivalent stiffness and damping of a nonlinear contact from the measured hysteresis loops. A numerical and experimental comparison of the variation in equivalent contact stiffness and damping has been described. Graphical abstract: Abstract: In the field of turbomachinery, one of the prime design aspects is to avoid high cycle fatigue failure commonly caused by fluctuating forces on the blades. These fluctuating forces render a high amplitude vibration of the blades that can be mitigated by introducing devices such as under-platform dampers and shrouds in the blade assembly. These devices are quite efficient in limiting the vibration amplitude of the blade even at the high temperatures that are typical of turbines. However, nonlinear forces are developed at the contact and these nonlinear forces make numerical simulations challenging for the designers. Therefore, along with numerical computations, experimental evidences are necessary to understand the actual physics of the damper-blade interactions. This paper represents an experimental study of the effect of these nonlinear contact forces on the vibration amplitude of the blade The present investigation explores, for the first time, the contact forces and relative displacement between the damper-blade contact interface measured directly using a recently developed experimental setup. These measured forces and relative displacement are further post processed to compute the equivalent contact characteristics, namely equivalent contact stiffness and damping. The contact characteristics are then associated with the classically measured performance of the dampers defined by the variation in frequency response of the blade. The experimental work presented here provides one of the first investigations to relate the macro/global behavior of the blade-damper with the micro/local behavior of their contact.